The Potential Role of Antioxidants in the Treatment of Peripheral Arterial Disease: A Systematic Review - Shayan Keramat; Hiva Sharebiani; Malay Patel; Bahare Fazeli; Agata Stanek (MDPI AG, 2022)
Peripheral arterial disease (PAD) has a worldwide prevalence and is a significant cause of cardiovascular morbidity and mortality. Due to its high prevalence and higher rates of ischemic cardiovascular and lower-extremity events, its treatment is essential. Increased levels of oxidative stress cause disease. This review aimed to evaluate different studies of antioxidant treatments for PAD patients. A systematic search for relevant studies was performed on the PubMed, SCOPUS, and ScienceDirect databases, and 18 studies fulfilled the inclusion criteria. In total, 16.6% of the studies used natural antioxidants, and 83.3% used synthetic antioxidants. The reviewed studies show that natural antioxidants were completely effective in treating PAD, and synthetic antioxidants showed effective results in only 53% of the studies. A less-than-optimal pro-oxidant-antioxidant balance does not improve the symptoms of PAD. In conclusion, antioxidants in their natural forms are more effective for PAD patients, and ensuring the optimal pro-oxidant-antioxidant balance is an effective method for managing treatment with antioxidants.